WUJUD SATUAN LINGUAL METAFORA POLITIK - Hari Kusmanto Kusmanto (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2021)
political contestation in 2019 uses a lot of metaphor as a means of communication. The problem is how does the media provide the forms of metaphor. This study aims to describe the lingual form of political discourse reported by online media Tribunnews.com. The research method used is descriptive qualitative. The data in this study are words, phrases, and metaphorical sentences reported by online media Tribunnews.com. The data source in this study is the title of the news on Tribunnews.com online media. Analysis of the data in this study uses the Agih method with the Direct Element technique (BUL). The results of this study indicate that the lingual unit form of metaphorical discourse includes: (1) nouns, verb words, and adjective words; (2) noun phrases, verb phrases, and adjective phrases; and (3) imperative sentences and declarative sentences. This shows that many metaphorical powers are chosen in political communication to convey indirect speech intentions.